Game design workshop a playcentric approach to creating innovative games - Fullerton, Tracy; Swain, Christopher, 1966-; Hoffman, Steven, 1965- (Amsterdam ; Boston : Elsevier Morgan Kaufmann, 2008)
Master the craft of game design so you can create that elusive combination of challenge, competition, and interaction that players seek. This design workshop begins with an examination of the fundamental elements of game design; then puts you to work in prototyping, playtesting and redesigning your own games with exercises that teach essential design skills. Workshop exercises require no background in programming or artwork, releasing you from the intricacies of electronic game production, so you can develop a working understanding of the essentials of game design. Features: * A design methodology used in the USC Interactive Media program, a cutting edge program funded in part of Electronic Arts. * Hands-on exercises demonstrate key concepts, and the design methodology * Insights from top industry game designers, including Noah Falstein, American McGee, Peter Molyneux.
The Role of the Game Designer; The Structure of Games; Working with Formal Elements; Working with Dramatic Elements; Working with System Dynamics; Conceptualization; Prototyping; Digital Prototyping; Playtesting; Functionality, Completeness, and Balance; Fun and Accessibility; Team Structures; Stages of Development; The Design Document; Understanding the Game Industry -- ; Selling Yourself and Your Ideas to the Game Industry.
Includes bibliographical references and index.
Keywords: Computer games -- Programming; Computer games -- Design; Computer graphics; Electronic books